2020
DOI: 10.1021/acs.iecr.0c02125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydrodynamic Cavitation Devices Based on Linear and Swirling Flows: Degradation of Dichloroaniline in Water

Abstract: Hydrodynamic cavitation (HC) is being increasingly used for a wide range of applications including wastewater treatment. No systematic comparison of pollutant degradation performance of different HC devices is available. In this work, for the first time: a basis for comparing performance of HC devices and a systematic comparison of pollutant degradation performance of five different types of HC devices based on linear and swirling flows is presented. 2,4-Dichloroaniline (DCA) was selected as a model pollutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
(49 reference statements)
2
24
0
Order By: Relevance
“…Additionally increasing the volume of the aqueous phase may hinder interfacial transfer of S and oxidising species. Similar data was reported by Bhasarkar et al [19] who investigated water addition in a H 2 O 2 /CH 3 COOH system for different pollutants and concentrations, reporting a slight decline in oxidation of BT, 3-methyl thiophene and thiophene at 100 ppm, 300 ppm and 500 ppm compared to the system without water. Therefore, only H 2 O 2 and carboxylic acid was utilised hence forth.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally increasing the volume of the aqueous phase may hinder interfacial transfer of S and oxidising species. Similar data was reported by Bhasarkar et al [19] who investigated water addition in a H 2 O 2 /CH 3 COOH system for different pollutants and concentrations, reporting a slight decline in oxidation of BT, 3-methyl thiophene and thiophene at 100 ppm, 300 ppm and 500 ppm compared to the system without water. Therefore, only H 2 O 2 and carboxylic acid was utilised hence forth.…”
Section: Resultssupporting
confidence: 88%
“…The HC device used in this work was a stainless steel vortex diode with throat diameter, d t = 6 mm purchased from Vivira Technologies. More details on the geometry and flow characteristics of this device may be found in Simpson and Ranade [18] , [19] . Details of experimental set-up and performance of HC device in terms of degradation of organic pollutants may be found in earlier work [19] .…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to linear flow cavitation devices, such as orifice and Venturi, swirling flow cavitating devices (e.g., vortex diode), proved to have early cavitation inception that starts at a pressure drop below 100 kPa [ 52 ]. Throughout the research, it has been found that in the case of linear flow cavitation devices, such as orifice and Venturi, cavitation takes place close to the device walls, causing the erosion of the device and lowering the device’s effectiveness over time, meanwhile in swirling flows devices, the cavitation takes place away from the walls of the device [ 53 ].…”
Section: Hydrodynamic Cavitation-based Processes For the Treatment An...mentioning
confidence: 99%
“…However, these are still comprised of small constrictions present in the device that makes a premilling step necessary for handling biomass or solids containing sludge. Linear flow devices have also been converted to swirl flow devices using inline swirlers , to lower cavitation inception pressure and mitigate cavitation erosion. The problem of clogging would however still persist because of the presence of small holes.…”
Section: Hydrodynamic Cavitation For Intensifying Anaerobic Digestionmentioning
confidence: 99%